A Novel Methodology to Assess Seismic Resilience (SR) of Interconnected Infrastructures - Davide Forcellini (Applied Sciences, 2022)
Modern and smart cities are significantly vulnerable to natural hazard, and their functionality is based on resilient infrastructure systems. In particular, seismic resilience may be considered the ability to deliver services during and after hazard events. Therefore, it is fundamental to identify the most critical components within a system, especially when multiple infrastructure systems are interdependent. The paper aims to propose a novel methodology that consider interconnected infrastructures to assess seismic resilience that may be defined as a function that depends on time, and the different components are considered the functional dimensions. The proposed methodology may be applied for several typologies of infrastructures, specifically looking at the seismic resilience analyses related to transportation systems. A case study has been considered in order to apply the proposed formulation and to demonstrate the importance of considering interdependency in the assessment of the seismic resilience. Many stakeholders (infrastructure owners, public administrations, decision makers) may be interested in applying the methodology that could be used to study several applications.